Hospital competition and quality for non‐emergency patients in the English NHS. - Moscelli, Giuseppe; Gravelle, Hugh; Siciliani, Luigi (RAND Journal of Economics (Wiley-Blackwell), 2021)
We investigate the effect on the quality of three high‐volume non‐emergency treatments of a reform that relaxed restrictions on patient choice of hospital. We employ a quasi difference‐in‐difference strategy and use control functions allowing for patient selection into providers correlated with unobserved morbidity. Public hospitals facing more rivals reduced quality, increased waiting times, and reduced length of stay for hip and knee replacements. This is likely due to regulated prices implying larger losses on these treatments compared to coronary artery bypass grafts, where no effects were found. Our findings are robust to estimation methods and competition measures, allowing for private providers' entry.